The safety and efficacy evaluation of sodium-glucose co-transporter 2 inhibitors for patients with non-alcoholic fatty liver disease: An updated meta-analysis. Issue 4 (April 2022) - Mo, Manqiu; Huang, Zichun; Liang, Yuzhen; Liao, Yunhua; Xia, Ning
Abstract: Background: In recent years, sodium-glucose co-transporter 2 inhibitors (SGLT2is) have been increasingly used in the treatment of patients with non-alcoholic fatty liver disease (NAFLD). This updated meta-analysis aimed to evaluate the efficacy and safety of SGLT2is for patients with NAFLD. Methods: PubMed, Embase, Cochrane Library, Web of Science, Wan Fang, China National Knowledge Infrastructure and VIP databases were searched for relevant studies from inception to April 30, 2021. Values of weighted mean differences (WMDs) and risk ratios (RRs) were determined for continuous and dichotomous outcomes, respectively. Results: A total of 1, 498 patients with NAFLD from 20 studies were included for further analysis. Pooled analyses indicated significant improvements in body mass index [WMD: −0.84 kg/m 2, 95% CI (−1.09, −0.60)], alanine aminotransferase [WMD: −4.36 U/L, 95% CI (−7.17, −1.54)], aspartate aminotransferase [WMD: −2.94 U/L, 95% CI (−5.33, −0.55)], fasting plasma glucose [WMD: −4.08 mmol/L, 95% CI (−6.21, −1.95)] and fibrosis-4 index [WMD: −0.08, 95% CI (−0.11, −0.05)] following SGLT2i treatment ( p  < 0.01 for all above parameters). There was no significant difference in the incidence of total adverse events between the SGLT2i group and the control group (RR = 0.78, 95% CI (0.58, 1.06), p  = 0.11]. Conclusion: SGLT2is seem to be a promising treatment for patients with NAFLD to improve metabolic and fibrosis indexes without increasing the incidence of adverse events. Most included studies were conducted in NAFLD patients with diabetes. Therefore, the results of this meta-analysis are more applicable to the diabetic population.